Antimicrobial resistance pattern of Bacteria isolated from ICU patients with respiratory tract infections (Dhaka University Journal of Pharmaceutical Sciences, 2015)
A total of 58 samples of respiratory tract infection (RTI) patients were collected from intensive care unit of three Dhaka based hospitals namely National Institute of Diseases of the Chest and Hospital (NIDCH), City Hospital (CH) and Japan Bangladesh Friendship Hospital (JBFH). Out of 58 samples studied, 47 (81.03%) samples showed growth of organisms identified as Staphylococcus aureus (n=24, 51.06%), Pseudomonas aeruginosa (n=9, 19.15%), Klebsiella pneumoniae (n=7, 14.89%), Streptococcus pneumoniae (n=3, 6.38%), Escherichia coli (n=2, 4.26%), Citrobacter (n=1, 2.13%) and Shigella (n=1, 2.13%). Most of the isolates were found resistant to piperacillin/tazobactam. All the isolates of S. pneumoniae (n=3), P. aeruginosa (n=9), K. pneumoniae (n=7), E. coli (n=2), Citrobacter (n=1), and Shigella (n=1) showed 100% resistance to piperacillin. S. aureus showed 79.17% resistance to piperacillin. Most of the isolates were 100% sensitive to imipenem, whereas S. aureus was only 91.67% sensitive to it. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21900 Dhaka Univ. J. Pharm. Sci. 13(2): 193-197, 2014 (December)